Circulating free DNA as a diagnostic marker for echinococcosis: a systematic review and meta-analysis - Luo, Xiaoqin; Jiang, Ping; Ma, Jideng; Li, Zian; Zhou, Jianwu; Wei, Xiaoxing; A, Jide; Chai, Jinping; Lv, Yanke; Cheng, Peng; Cao, Chunhua; A, Xiangren (Frontiers in Microbiology, 2024)
Introduction Echinococcosis is a chronic zoonotic disease caused by tapeworms of the genus Echinococcus. The World Health Organization (WHO) has identified encapsulated disease as one of 17 neglected diseases to be controlled or eliminated by 2050. There is no accurate, early, non-invasive molecular diagnostic method to detect echinococcosis. The feasibility of circulating free DNA as a diagnostic method for echinococcosis has yielded inconclusive results in a number of published studies. However, there has been no systematic evaluation to date assessing the overall performance of these assays. We report here the first meta-analysis assessing the diagnostic accuracy of cfDNA in plasma, serum, and urine for echinococcosis. Methods We systematically searched PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI), and WeiPu databases up to 17 January 2024, for relevant studies. All analyses were performed using RevMan 5.3, Meta-DiSc 1.4, Stata 17.0, and R 4.3.1 software. The sensitivity, specificity, and other accuracy indicators of circulating free DNA for the diagnosis of echinococcosis were summarized. Subgroup analyses and meta-regression were performed to identify sources of heterogeneity. Results A total of 7 studies included 218 patients with echinococcosis and 214 controls (156 healthy controls, 32 other disease controls (non-hydatid patients), and 26 non-study-targeted echinococcosis controls were included). Summary estimates of the diagnostic accuracy of cfDNA in the diagnosis of echinococcosis were as follows: sensitivity (SEN) of 0.51 (95% CI: 0.45–0.56); specificity (SPE) of 0.99 (95% CI: 0.97–0.99); positive likelihood ratio (PLR) of 11.82 (95% CI: 6.74–20.74); negative likelihood ratio (NLR) of 0.57 (95% CI: 0.41–0.80); diagnostic ratio (DOR) of 36.63 (95% CI: 13.75–97.59); and area under the curve (AUC) value of 0.98 (95% CI: 0.96–1.00). Conclusion Existing evidence indicates that the combined specificity of circulating cfDNA for echinococcosis is high. However, the combined sensitivity performance is unsatisfactory due to significant inter-study heterogeneity. To strengthen the validity and accuracy of our findings, further large-scale prospective studies are required. Systematic review registrationThe systematic review was registered in the International Prospective Register of Systematic Reviews PROSPERO [CRD42023454158]. https://www.crd.york.ac.uk/PROSPERO/.